THE INTERACTION BETWEEN PUBLIC AND FACT-CHECKING CONTENT: THE PERCEPTION OF LUPA’S COMMENTERS ABOUT POLITICAL DEBATES DURING 2022 PRESIDENTIAL ELECTION IN BRAZIL - Anastacio, Thiago Fedacz; Tavares, Camilla Quesada (AoIR Selected Papers of Internet Research, 2026)
This study examines how citizens engage with fact-checked content provided by fact-checking agencies. Specifically, it focuses on fact-checks conducted by the Lupa agency regarding the debates held during the 2022 Brazilian presidential elections. Lupa is one of the first fact-checking agencies in Brazil. Founded in 2015, it is a member of the International Fact-Checking Network (IFCN), a global organization affiliated with the Poynter Institute in the United States. Comments from three fact-checking posts were collected from the agency’s official Instagram profile. In total, 1,222 comments from posts analyzing the debates broadcast by SBT, Band, and Globo were examined. A textual analysis was conducted using the Iramuteq software, employing similarity analysis, Reinert classification and word cloud generation. The findings indicate that discussions in the comment section leverage candidates’ statements and their fact-checks to debate issues that extend beyond the content published. Additionally, users criticize Lupa’s fact-checking process, highlighting areas that should be improved in the verification and dissemination of information. Some comments also reference the labels used by the agency to classify content. As the analyses reveal, commenters frequently question and challenge these labels used to determine the truthfulness of statements. In the next phase of the research, a categorical content analysis will be conducted to gain a more detailed understanding of user interactions.